Implementasi Metode Apriori Dalam Pembagian Kejuruan Penerimaan Siswa Baru Di SMK Negeri 1 Siantar - Saragih, Ria Annisa; Damanik, Irfan Sudahri; Saragih, Ilham Syahputra (STIKOM Tunas Bangsa Pematangsiantar, 2021)
The purpose of this research is to determine the vocational division of the acceptance of new students that will be taken by the author with data mining techniques using a priori algorithm method. The data source used is to make observations. Match predictions can be obtained based on the results of comparisons with other students who have similarity data with student A. By using a priori algorithm obtained results that involve a collection of items that often with a high value of trust. The results of this study are data that group prospective new students based on their desired majors with a minimum support of 50% and a minimum trust of 50%, making 20 rules that are set aside. One of the rules that is formed is if the student chooses a fashion major (A4) then the department that is more suitable for students is hair and skin (A2) with a support value of 0.5 or equal to 50 and trust 100 to 0.5 or equal to 50 It is hoped that this information can provide advice to the public vocational school 1 Siantar.